Gyriform restricted diffusion in adults: looking beyond thrombo-occlusions - Pai, Vivek (Insights Imaging, 2020)
Gyriform restricted diffusion (GRD) refers to hyperintense signal involving the cerebral cortex on diffusion-weighted images (DWI) with corresponding hypointensity on apparent diffusion coefficient (ADC) images. These changes are commonly seen following a vascular occlusion, reflecting the limitation of water molecule movement across cell membranes (restricted diffusion) due to the failure of Na(+)/K(+)-ATPase pumps (cytotoxic oedema). However, GRD can occur in several other neurological conditions as well. A thorough understanding of these conditions and their anatomic predilection plays a critical role in identifying and differentiating them from vascular thrombo-occlusion, with impact towards appropriate clinical management. This review highlights the less commonly encountered, non-stroke causes of GRD in adults with case-based examples. A tabulated chart of the patterns of cortical and subcortical involvement associated with these aetiologies is provided for a quick, pattern-based reference for daily radiological reporting.